Quality of water produced by air conditioning equipment for non-potable purposes - Melo, Allan Jayson Nunes de; Soares, Maria Carolina Duarte Marques; Silva , Simone Rosa da; Soares, Willames de Albuquerque (Periódico Eletrônico Fórum Ambiental da Alta Paulista, 2022)
Air conditioner is an equipment which is      present in most buildings around the world, either serving to provide greater thermal comfort to its users, or as part of industrial processes. This equipment while in operation produces water from the condensation of the air in contact with its coil, which has the potential to be used for non-potable purposes       within the buildings. This study aims to evaluate the quality of condensate water from air conditioners for non-potable purposes. Water collection was carried out in the water harvesting system of a hospital type building located in the city of Recife-PE, Brazil. The applied methodology analyzed the physicochemical parameters that include: pH, color, odor, turbidity, electrical conductivity, total dissolved solids, ammonia, nitrite, nitrate, alkalinities, total hardness, carbonate hardness, non-carbonate hardness, chloride, sulfate, carbonate, bicarbonate, calcium, magnesium, sodium, potassium, total iron, manganese and, in the microbiological analysis, the presence of coliforms. In addition, the applied methodology       compared the results of this and other studies found with the same theme, with the maximum limits provided for in Ordinance No. 888/2021 of the Ministry of Health of Brazil. The results showed an excellent quality of the condensate water, approaching in most parameters of      drinking water, and thus, it can be used for non-potable purposes       such as: garden irrigation, floor washing, replacement in cooling towers, among others.